2015
DOI: 10.1007/s12529-015-9519-6
|View full text |Cite
|
Sign up to set email alerts
|

Do Flexible Goal Adjustment and Acceptance Help Preserve Quality of Life in Patients with Multiple Sclerosis?

Abstract: The authors declare that they have no conflict of interest.All procedures performed in studies involving human participants were in accordance with the ethical standards of the institutional and/or national research committee and with the 1964 Helsinki declaration and its later amendments or comparable ethical standards. Informed consent was obtained from all individual participants included in the study. 2 Abstract PurposeAcceptance and flexible goal adjustment are believed to be protective factors in chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 57 publications
2
23
1
Order By: Relevance
“…Firstly, the dual process model [ 9 ] differentiates two complementary strategies: the assimilative mode (tenacious goal pursuit), which is directed at maintaining goals by intentional efforts that modify the actual situation in accordance with personal goals, and the accommodative mode (flexible goal adjustment), which is directed at adjusting goals to situational or physical constraints. Several studies in patients with a range of chronic conditions, including chronic pain, have found that the combined use of accommodative and assimilative strategies was associated with well-being [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the dual process model [ 9 ] differentiates two complementary strategies: the assimilative mode (tenacious goal pursuit), which is directed at maintaining goals by intentional efforts that modify the actual situation in accordance with personal goals, and the accommodative mode (flexible goal adjustment), which is directed at adjusting goals to situational or physical constraints. Several studies in patients with a range of chronic conditions, including chronic pain, have found that the combined use of accommodative and assimilative strategies was associated with well-being [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Support for the adaptive nature of acceptance is far‐reaching, as acceptance has demonstrated positive effects on quality of life for a number of patient and disability groups (Kratz, Hirsh, Ehde, & Jensen, ; McCracken & Eccleston, ; Van Damme, De Waegeneer, & Debruyne, ). Similar to other health conditions, there is also evidence to suggest that acceptance following the loss of hearing and/or vision can be adaptive for psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectionally, there is evidence showing that pain is associated with depressive symptoms. 13,14 This association is often explained by the fact that increased pain is associated with impaired functioning. This in turn is linked to more depressive symptoms.…”
Section: Previous Research and Possible Explanationsmentioning
confidence: 99%
“…With regard to FGA, a few cross-sectional studies have examined the association between FGA and outcomes such as negative emotions or depressive symptoms. 8,9,13,14,28 One of those cross-sectional studies, for instance, found that FGA was associated with reduced depression in Twente, Netherlands (n = 305). 28 Based on rather small samples in other countries, similar findings were made, for example, by Boerner 14 (n = 107; USA), Van Damme 13 (n = 117; Belgium) and Schmitz 9 (n = 118; Germany).…”
Section: Previous Research and Possible Explanationsmentioning
confidence: 99%